THEORETICAL FOUNDATIONS OF AN INTEGRATIVE APPROACH TO DESIGNING THE CONTENT OF PRIMARY SCHOOL EDUCATIONAL MATERIALS (International journal of artificial intelligence, 2026)
This article examines the theoretical foundations of the integrative approach in designing the content of primary school learning materials. The integrative approach aims to connect different subject areas in order to form a holistic system of knowledge among pupils. The concept of pedagogical integration, its didactic value, and its role in the modern educational process are analyzed. The study emphasizes that integrated learning materials contribute to the development of logical thinking, problem-solving skills, independent learning abilities, and the practical application of knowledge. Furthermore, integrative content increases students’ motivation, enhances their interest in learning, and supports the formation of key competencies. The article concludes that the integrative approach serves as an effective methodological basis for improving the quality of primary education and for ensuring the continuity and coherence of learning outcomes.